Surface modification of carbon fiber for improving the interfacial adhesion between carbon fiber and polymer matrix†. (11th November 2015) - Rahmani, Hossein; Ashori, Alireza; Varnaseri, Najmeh
Abstract : In this study, the reinforcing mechanism of amine functionalized on carbon fibers (CFs) has been precisely discussed, and the differences between aliphatic and aromatic compounds have been illustrated. Polyacrylonitrile‐based CFs were functionalized with ethylenediamine, 4, 4‐diaminodiphenyl sulphone, and p ‐aminobenzoic acid (PAB), and CF‐reinforced epoxy composites were prepared. The structural and surface characteristics of the functionalized CFs were investigated using X‐ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT‐IR), and scanning electron microscopy (SEM). Mechanical properties in terms of tensile and flexural strengths and moduli were studied. The FT‐IR results confirm the success in bonding amines on the CF surface. After treatment of CFs, the oxygen and nitrogen contents as well as the N/C ratio showed an increase. XPS results provided evidence of the chemical reaction during functionalization, rather than being physically coated on the CF surface. Chemical modification of CF with diamines led to considerable enhancement in compatibility of CF filaments and epoxy resin, and remarkable improvements were seen in both tensile and flexural properties of the reinforced composites. SEM micrographs also confirmed the improvement of interface adhesion between the modified CFs and epoxy matrix. Finally, it can be concluded that PAB is a promising candidate to functionalize CF in order to improve interfacial properties of CF/epoxy composites. Copyright © 2015 John Wiley & Sons, Ltd.